Comparative evaluation of three methods of endotracheal tube cuff inflation for adequacy of seal - M V. S Satya Prakash; C Aravind; V K Mohan (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Intubation with cuffed endotracheal tube (ETT) is common in operation rooms, critical care, and emergency rooms. The pressure exerted by the cuff on the tracheal mucosa can lead to a reduction in blood flow to the tracheal wall and result in mucosal ischemia. There are many methods for ETT cuff inflation. Aim of the study was to compare the cuff pressures and volumes between the three methods of ETT cuff inflation. Material and Methods: One hundred and twenty patients were randomized into three groups: Group SG (stethescope guided), group AL (audible leak), and group P (palpation). In group SG, the cuff was inflated by auscultating with the bell of the stethoscope over the thyroid cartilage for leak around cuff. In group AL, the cuff was inflated by listening for an audible leak around the cuff with observer's ear 5 cm away from the mouth of the patient. In group P, the cuff was inflated by palpating for a leak over the cricoid and trachea. The adequacy of the cuff seal was compared between the groups by assessing the volumes of additional air needed to stop the leak around the cuff as confirmed by supraglottic capnometry. Results: The initial volumes needed to inflate the cuff were significantly more in the stethoscope (SG) and hearing (AL) groups than in the palpation (P) group (SG = 5.1 ± 1.4 ml, AL = 4.6 ± 1.6 ml, P = 3.1 ± 0.9 ml; SG and AL vs. P, P < 0.001). Additional cuff volumes required to achieve zero leak around cuff by supraglottic capnometry were 0.85 ± 1 ml in group SG, 1.3 ± 1.1 ml in group AL, and 2.237 ± 0.8 ml in group P (SG vs. P and AL vs. P; P < 0.001). Conclusion: Out of the auscultation-guided, audible leak-guided, and palpation-guided methods of ETT cuff inflation, the auscultation-guided and audible leak-guided methods achieve significantly better tracheal seal than the palpation-guided method.